ANALISIS RESPON MASYARAKAT SUDIANG TERHADAP RENCANA REVITALISASI GELANGGANG OLAHRAGA SUDIANG SEBAGAI OBJEK WISATA BERBASIS KOMUNITAS - Ardiansyah, Ardiansyah; Syukur, Idris; Mutmainnah, Mutmainnah (Nature : National Academic Journal of Architecture, 2014)
Sudiang sports center is one of the architectural masterpiece that is purposedly built to be used optimal by the local society, but thee reality is far from what is expected. Next problem is many street vendors who sell around the gymnasium building and road shoulders so that the building is supposed to be a place to exercise converted into a sale and purchase. The author tries ries to analyze and provide solutions through revitalization plan as a sports center attaractions based community efforts to address the problem. Through this research will be know apperenciation of the local society on the plan and will be know the factors cousing problem arise, trough a questionnaire which contains several points and sub questions that are  considerd related to the issue above the level of public enthusiasm and response plan as well as an opportunity to serve as a tourist destination. Then the data will be processed by presented using MS Excel based as the highest answer and lowets voting, the reslts of research state that the dominant factor that couses people rarel visit was the lack of free time due to the business of the work and the generally public to respond and respond positively on a revitalization plan. Therefor the relevant stakeholders such as the such as the society is expented to be more enthusiastic about building of Sudiang sports center as better an for the manager of the building with geverment in order to improve the quality of service and wise in making decisions in terms of regulating street vendors.